PENGEMBANGAN MODEL PEMBELAJARAN MELEK MEDIA TELEVISI - Arifah Bintarti; Udin S Winataputra; Nila Kusuma Windrati; Mani Festati Broto; Yulia Budiwati (LPPM Universitas Terbuka, 2011)
One attempt to control the negative effects of television (TV) is to educate parents about the TV media and programs. TV media literacy for parents is needed, so that they as chaperone for their children have the ability to filter messages from TV programs, translate and interpret in accordance with the moral values. This study were aimed to survey media literacy of parents and develop media literacy learning for parents. The populations in this study were the parents of elementary school students of grades 4, 5, and 6 in the South Tangerang for the two districts, namely District of Ciputat and District Setu. Samples were taken purposively of 283 respondents. Data were collected through questionnaires and interviews of 20 respondents in the activities of Focus Group Discussion. The process consisted of three stages, namely the survey, model development, and testing models. All three phases of activity showed the following results. Most of the respondents were knowledgeable about the TV program, and the values contained in the message of the TV program watched by their children. However, some respondents were misunderstood and unsure about the moral values contained in the TV program, so that their attitudes toward the TV programs watched by their children were loose. The second phase was built a learning model in multimedia package with a video format, which presented snippets of TV programs, and guidances from communication experts and child psychologists. This model is presented to respondents in the first focus group discussion. The next phase, the second focus group discussion was conducted to see changes in knowledge and attitudes of parents after receiving the learning model. The results showed that there were changes in knowledge and attitudes of parents about the TV programs watched by their children.